A meta-model of software development project states behavioral study of software projects - Akbar, R. (John Wiley and Sons Ltd, 2017)
Software development project during its lifecycle passes through various states. These states describe the condition, status, and behavior of software projects. In the present study, these states are defined based on the various activities performed during project lifecycle like initial environment setup, requirement analysis, coding, testing, problem resolution, and completion. The taxonomy of these states and substates is defined, and a project states meta-model is designed. The meta-model is composed of states and substates of the software projects. Detailed case studies of real projects have been conducted to validate the states of the meta-model. Evidences are collected; and events and observations are recorded about existence of the states, execution flow, duration, and behavior. The evidences, events, and observations are presented in the sequence to translate them into results. Results show that project states exist in all projects such that each software project passes through these states serially and in particular cases, a few states may exist in parallel. Project states show the status and progress of the software projects. It is found that issues in software projects can effectively be resolved by performing micro project management activities of the projects states. Project states meta-model provides basic structure for deriving new models. Copyright © 2016 John Wiley & Sons, Ltd.